2010
DOI: 10.1002/cphc.201000469
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Reactions of Peroxy Radicals in Atmospheric Chemistry and Combustion

Abstract: Peroxy radicals can undergo isomerisation and dissociation reactions in competition with reactions with NO and with other peroxy radicals. Such a competition is central to the recently proposed mechanism for OH regeneration in the atmospheric oxidation of isoprene. The occurrence of peroxy radical isomerisation reactions in both combustion and atmospheric chemistry is discussed, and exemplified by reference to the peroxy radicals formed from the C(2)H(5), CH(3)CO, HO-C(2)H(2) and HO-C(6)H(6) radicals. The disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 39 publications
0
93
1
Order By: Relevance
“…However, the fast reaction with O 2 is the major consumption step, even at higher temperatures. Alzueta et al identified the chain‐propagating sequencetruerightC2H2+ OH C2H2 OH +O2 OCHCHO + OH as important for the onset of reaction for C 2 H 2 at atmospheric pressure and temperatures above 700 K. Interest in this oxidation pathway for atmospheric chemistry has spawned a range of experimental and theoretical studies on the C 2 H 2 + OH + O 2 reaction at low temperature . Hatakeyama et al showed in smoke‐chamber experiments that the reaction generates glyoxal and formic acid,trueright CHCHOH +O2 OCHCHO + OH trueright CHCHOH +O2 HOCHO + HCO …”
Section: Detailed Kinetic Modelmentioning
confidence: 99%
“…However, the fast reaction with O 2 is the major consumption step, even at higher temperatures. Alzueta et al identified the chain‐propagating sequencetruerightC2H2+ OH C2H2 OH +O2 OCHCHO + OH as important for the onset of reaction for C 2 H 2 at atmospheric pressure and temperatures above 700 K. Interest in this oxidation pathway for atmospheric chemistry has spawned a range of experimental and theoretical studies on the C 2 H 2 + OH + O 2 reaction at low temperature . Hatakeyama et al showed in smoke‐chamber experiments that the reaction generates glyoxal and formic acid,trueright CHCHOH +O2 OCHCHO + OH trueright CHCHOH +O2 HOCHO + HCO …”
Section: Detailed Kinetic Modelmentioning
confidence: 99%
“…By comparison, the canopy-averaged total OH production rate in the base scenario is 3.8 pptv s −1 . It is possible that our simple mechanism has neglected additional sinks of VRO 2 radicals, such as unimolecular isomerization/decomposition (Glowacki and Pilling, 2010) or surface deposition, which would reduce the buildup of VRO 2 in the canopy. For example, VRO 2 concentrations decrease by 20 % when we force VRO 2 to deposit at the aerodynamic limit, though even this loss would be insufficient to bring the modeled NO/NO 2 ratio for the y = 0.75 case into the range expected for this forest.…”
Section: Ro X Chemistrymentioning
confidence: 99%
“…The addition of the OH radical to the aromatic ring results in the formation of a hydroxycyclohexadienyl-type radical (Bohn, 2001;Molina et al, 1999). Under atmospheric conditions this reacts with O 2 to yield peroxy radicals or phenolic compounds (Calvert et al, 2002;Glowacki and Pilling, 2010;Suh et al, 2003). When aromaticity is lost by OH addition, nonaromatic double bonds are formed representing highly reactive products to more oxidants, which is a peculiar behavior not observed in other classes of VOCs (Calvert et al, 2002), This behavior makes the investigation of ArHC oxidation more complex.…”
Section: Introductionmentioning
confidence: 99%